Evaluación al sistema del banco comunitario "Sembrado en Cristo" para fortalecer el capital patrimonial y su otorgamiento de créditos en el sector financiero popular y solidario de los agricultores en el Cantón Ventanas a partir del 26 de enero del 2011 - Magullón Burgos, Karen Paola (2012)
Whereas Community Bank "Sowing in Christ" is a de facto association with indefinite duration, business-like, with popular character capital contributions made by individual. The same that began with an administrative structure such as: The general meeting of members, the board of directors, the credit committee and special committees are appointed. Considering that the general meeting of shareholders is the highest authority, the Board is composed of five members, the credit committee is responsible for qualifying credit applications, and special committees and monitors compliance with the mandated purposes . Most of the members of the Community Bank "Sowing in Christ" has become secondary preparing a fortress, from having knowledge of the partners. Most of the members of the Community Bank "Sowing in Christ" made monthly savings between 100 to 200 dollars, which is essential for the functioning of the EU financial system. The Community Bank "Sowing in Christ" only works with farmers in the sector and has no other lines to other segments that generate more income to the institution. Currently has improved the economic situation of the partners with the help of the community bank providing credit either for productive consumption area and pop.